HUBUNGAN ANTARA KREATIVITAS DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR BAHASA INGGRIS - Moh Fahri Yasin; Muhammad Akbar (Akademika, 2017)
This article discusses the correlation between creativity and selves study withresult of study on social the objectives of this research are : 1) Finding out the correlationbetween students’ creativity and study result on English subject. 2) Finding out thecorrelation between students’selves-study and study result on English subject. 3) Findingoutthecorrelationbetweenthestudents’studycreativityandselves-study all together withthe study result on English subject.The problems of this research are : 1) is there positivecorrelationbetweenstudents’creativityandstudyresultonEnglishsubject.2)is there apositivecorrelationbetweenstudent’sselves-study and study result on English subject. 3) isthere a positive correlation between the students’ study creativity and selves-study alltogether with the study result on English subject. The research method applied in thisresearch is survey research method, the target of population is the whole of the eighth gradestudents’of junior high school at SMP Negeri di Kota Bekasi, and the achievable populationis 122 students. The sample is taken using the Slovin formula. Based on the data analysis,there is a positive correlation between students’ creativity and study result on Englishsubject with correlation coefficient of product moment 0,46. There is positivecorrelation between students’ selves-study and study result on English subject withcorrelation coefficient of product moment 0,137. There is positive correlation betweenthestudents’studycreativity and selves-study all together with the study result on Englishsubject with the double correlation coefficient . 0,149. The conclusion of this researchis that the high result of study on English subject will be gained if the students have highcreativityonthestudysupportedbythestudents’selves-study. The is expected to grow thestudents’creativityandisexpectedtobeabletousethevariouskindsoflearningmethodswhich are oriented to the students